2022
DOI: 10.3390/ma15155111
|View full text |Cite
|
Sign up to set email alerts
|

Glass Fibers Reinforced Concrete: Overview on Mechanical, Durability and Microstructure Analysis

Abstract: Prior studies in the literature show promising results regarding the improvements in strength and durability of concrete upon incorporation of glass fibers into concrete formulations. However, the knowledge regarding glass fiber usage in concrete is scattered. Moreover, this makes it challenging to understand the behavior of glass fiber-reinforced concrete. Therefore, a detailed review is required on glass fiber-reinforced concrete. This paper provides a compressive analysis of glass fiber-reinforced composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 83 publications
6
39
0
1
Order By: Relevance
“…Saleem investigated CFRP application and the reinforcement ratio in reinforced concrete beams, and the results were presented in terms of moment–curvature values, ultimate load, and failure patterns. It was noted that the failure modes of beams are dependent on the CFRP layout [ 8 ]. Qureshi studied the flexural and shear strains of polymer composites at the bonding interface of epoxy and concrete and found that the strength increment in flexural members depends on the values of the strains in the CFRP [ 4 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Saleem investigated CFRP application and the reinforcement ratio in reinforced concrete beams, and the results were presented in terms of moment–curvature values, ultimate load, and failure patterns. It was noted that the failure modes of beams are dependent on the CFRP layout [ 8 ]. Qureshi studied the flexural and shear strains of polymer composites at the bonding interface of epoxy and concrete and found that the strength increment in flexural members depends on the values of the strains in the CFRP [ 4 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concrete is a widely used construction material in building infrastructure all around the world owing to its ability to be cast into shape, durability, cost-effectiveness, and high compressive strength [ 1 , 2 , 3 ]. Poor quality control during the construction process; the corrosion of steel reinforcement; design errors; natural disasters such as earthquakes, explosions, and hurricanes; and harsh environments are some major factors that degrade the durability and strength of reinforced concrete (RC) structures during their design life [ 2 , 4 , 5 , 6 , 7 , 8 , 9 ]. Demolishing and rebuilding or adding extra structural members to enhance the strength of a concrete structure is often regarded as an uneconomical and unsustainable strategy and thus requires huge investments [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By changing the traditional and energy-intensive techniques of using steel reinforcing bars and wire mesh with fibers, building costs may be reduced overall [ 17 , 18 , 19 ]. Therefore, labor expenses will be cheaper, as will upkeep expenses, the amount of time needed for construction, and the overall cost of the building.…”
Section: Introductionmentioning
confidence: 99%